(961) Health planning ; a challenge to developing nations التخطيط الصحي؛ تحدٍّ يواجه الدول النامية - W.A Hassouna M.D (معهد التخطيط القومي, 2026)
ملخص This study examines the structural and methodological dimensions of "health planning" as a critical cornerstone and a major challenge facing socio-economic development in developing countries. The author explicitly rejects the mechanical application of Western industrialized development models, arguing that they are inherently "culture-bound" and unsuitable for the distinct socioeconomic realities of Asian and African nations. Instead, the paper advocates for an "inductive or clue-seeking approach" to goal identification, which derives planning strategies directly from the felt needs, environment, and observed necessities of the local population, rather than imposing top-down deductive frameworks that alienate the public. The monograph is structured into three pivotal sections. Sections I and II conceptualize health development goals, resource allocation, service delivery systems, and implementation evaluation. The author emphasizes the reciprocal relationship between health and productivity, demonstrating that health services function as an "education for development" by transforming traditional attitudes toward life expectancy and causation. This shift enhances individuals' sense of personal efficacy and empowers them to engage in long-term economic planning and investment in human capital. Section III presents an empirical case study of Egypt (then the United Arab Republic), analyzing demographic background data, rapid population growth rates, and prevailing disease patterns. The study culminates in strategic recommendations for formulating realistic, dynamic national health plans integrated with feedback mechanisms to optimize societal well-being. تتناول هذه الدراسة الأبعاد الهيكلية والمنهجية لعملية "التخطيط الصحي" باعتبارها ركيزة أساسية ومتحدياً حرجاً يواجه التنمية في الدول النامية. يرفض الكاتب صراحةً تبني النماذج التنموية الغربية الجاهزة (المعلّبة)، واصفاً إياها بأنها "مقيدة ثقافياً" ولا تتلاءم مع البيئات المحلية للدول الإفريقية والآسيوية. بدلاً من ذلك، يدعو البحث إلى تبني "المنهج الاستقرائي القائم على استقراء القرائن والمؤشرات اللمسيّة" لتحديد الاحتياجات الفعلية والواقعية للمجتمع من واقع بيئته، بدلاً من المنهج الاستنباطي الفوقي الذي يخلق فجوة بين المخطط والمجتمع وينقسم البحث إلى ثلاثة محاور رئيسية؛ يناقش الأول والثاني تحديد الأهداف التنموية الصحية، وتخصيص الموارد، والآليات الفعّالة لتقديم الخدمات الصحية ومتابعتها وتقييمها. ويركز البحث على العلاقة العضوية بين الصحة والإنتاجية، مبيناً أن الخدمات الصحية تعمل بمثابة "تعليم من أجل التنمية" عبر تغيير السلوكيات التقليدية والمفاهيم السائدة حول مسببات الأمراض ومتوسط العمر المتوقع، مما يمنح الأفراد شعوراً بالقدرة الفردية والتحكم في مستقبلهم، وهو جوهر التنمية البشرية المستدامة وضخ الاستثمارات في رأس المال البشري. أما المحور الثالث، فيستعرض دراسة حالة تطبيقية على جمهورية مصر العربية (الجمهورية العربية المتحدة آنذاك)، محللاً البيانات الديموغرافية، التحديات الهيكلية مثل النمو السكاني المتسارع، وأنماط الأمراض السائدة، مختتماً بتقديم توصيات عملية لصياغة خطط صحية مرنة وقابلة للتعديل بناءً على التغذية الراجعة المستمرة من البيئة المحلية المستهدفة.